Surveillance of Occupational Risks Using Job-Exposure Matrices - Martin, J. M.; Mouaddib, A.; Huy-Simon, C.; Robaux, P. (Methods of Information in Medicine, 1991)
This article deals with the problem of surveillance of occupational risks of workers. Computer-assisted elaboration of the job history (JH) for each worker was achieved by means of a job-exposure matrix (JEM) for each company. The final aim of the project is to find correlations between the exposure data of JHs and the health data of corresponding medical records.As a first experiment, some JEMs were computed using rectangular arrays even though it was realized that this simple structure was not really adequate. Later on, the structure of the computerized JEM included the following questions: (1) what types of information are involved; (2) how can the job-exposure correspondence be represented in the computer; (3) what characteristics of a company should be used for the elaboration of a JEM; (4) who is to construct each JEM, and how? This article shows the inadequacy of some occupational names for evoking the appropriate risks, a drawback which can be surmounted if the company organization is included in the JEM. Based on our analysis, several specifications useful for JEM computerization have been suggested.
Keywords: Job-Exposure Matrix; Job History; Surveillance; Occupational Risk Factors; Microcomputer